30,000 minimum wages: The economic effects of collective bargaining extensions - Pedro S. Martins (Global Labor Organization (GLO), 2019)
Many governments extend the coverage of collective agreements to workers and employ- ers that were not involved in their bargaining. These extensions may address coordination issues but may also distort competition by imposing sector-specific minimum wages and other work conditions that are not suitable for some firms and workers. In this paper, we analyse the impact of such extensions along several economic margins. Drawing on worker- and firm-level monthly data for Portugal, a country where extensions have been widespread, and the scattered timing of the extensions, we find that, while continuing workers experience wage increases following an extension, formal employment and wage bills in the relevant sectors fall, on average, by 2%. These results increase by about 25% across small firms and are driven by reduced hirings. In contrast, the employment and wage bills of independent contractors, who are not subject to labour law or collective bargaining, increases by over 1% following an extension.
Keywords: J52; K31; J23; 330; Collective agreements; Worker flows; Labour law